Managing Chronicity in Unequal States : Ethnographic perspectives on caring - Montesi, Laura; Calestani, Melania (Embodying inequalities., 2021)
Managing Chronicity in Unequal States investigates how people live with chronic conditions in different contexts around the world, where judgements on human worth have long-lasting effects on people's wellbeing.